Fatigue Performance of Welded Steel Girders with Corrugated Webs - Save, Erik; Åkermo, Karl (My University, 2020)
Steel girders with corrugated webs have been widely studied regarding their static capacity. They are known to have high out-of-plane stiffness as well as shear buckling capacity. This permits the use of deeper web plates without the need for additional stiffeners. However, an important aspect that has not been studied to a large extent is the fatigue capacity of these structures. A number of fatigue tests have previously been performed to determine their fatigue resistance. Those tests have shown the complexity of the fatigue performance due to the complex geometry and shear transfer mechanism. One aspect that is argued to influence the stress state is the transverse bending of the flanges due to shear flow in the web. This effect and its influence on the structural hot spot stress at fatigue critical points has not been examined until today and is therefore further investigated in this thesis. This thesis initially presents a state of the art literature review of previous work on fatigue performance of corrugated web girders followed by the procedure, results and discussion of the finite element analyses performed. Evaluation of previously performed experimental tests shows that the fatigue performance of corrugated web girders is slightly better than what is currently suggested in the design standard EN 1993-1-9. Based on the finite element analysis, it is found that the transverse bending of the flanges has an effect on the structural hot spot stress at the fatigue critical points and should be considered in fatigue design. A proposal is presented for considering the structural hot spot stress as a superposition of two parts corresponding to primary and transverse bending of the flanges. Also, suggestions on how to efficiently and accurately model a corrugated web girder using finite element method are given.
Keywords: Corrugated Web; Welded Steel Girder; Fatigue; Finite Element Modelling; Structural Hot Spot Stress; Transverse Bending